Answer:
3.75
Step-by-step explanation:
Answer:
(2 x)/15
Step-by-step explanation:
Simplify the following:
(4 x)/5 - (2 x)/3
Put each term in (4 x)/5 - (2 x)/3 over the common denominator 15: (4 x)/5 - (2 x)/3 = (12 x)/15 - (10 x)/15:
(12 x)/15 - (10 x)/15
(12 x)/15 - (10 x)/15 = (12 x - 10 x)/15:
(12 x - 10 x)/15
12 x - 10 x = 2 x:
Answer: (2 x)/15
Answer: The parabola opens upwards.
Step-by-step explanation:
Lets take (-4) - (-6)
= -4 + 6 (here we changed the sign because in integers when you are subtracting <span>an integer, we put its opposite..thats the rule .)
=. -4 + 6 = 2
so here we got the answer as 2 .....this shows that </span>your answer will be less than the integer you started with ....this is because here in subtraction we will first change the sign and then follow the same rules of addition ...so here if both the numbers have opposite signs then we subtract and put the greater number sign .....
<span>
Hope i am right !!!</span>
The slope of x-y=8 is 1 because it's actually y = x-8
Parallel means the slope is equal to 1 as well.